Examine the environmental inequity impact of urban heat mitigation on redlining legacy: case study of Charlotte’s retrofitting, 2001–2020 - Li, Xijing; Ma, Xinlin; Lyu, Fangzheng; Song, Yan (Frontiers in Environmental Science, 2023)
Climate adaptation policies have received attention in major due to the dual challenges of external factors like global warming, and internal factors related to the transition from rapid urbanization to sustainable development. However, previous research on heat or climate mitigation has often focused on external factors, neglecting the internal factors throughout the process of urban development and planning history. Research has revealed that city center where urban heat island phenomena is prominent, are subjected to external factors of intense heat exposure, as well as deeply influenced by the internal factors “urban development legacy”. An increasing body of research note that the inequitable legacy from urban development could impact environmental equity outcomes of cities. Based on this, we argue that urban heat mitigation research should adopt the perspective of the urban development process. We then utilize the Heat Mitigation Framework to examine the tangible outcomes of environmental equity over an extended period of urban development. This study focuses on the Charlotte city center that have undergone multiple processes of redlining policies and rapid urbanization, using a research framework for environmental equity-oriented urban heat management to examine whether a series of heat mitigation policies have effectively reduced heat exposure and whether they have truly benefited heat-vulnerable groups. Based on 20 years of multi-source heat exposure and urban spatial data, this paper provides evidence of ongoing enhancements to the heat exposure environment in the Charlotte city center. However, despite these improvements, heat vulnerable group that are particularly susceptible to the negative effects of heat exposure did not experience commensurate benefits. The conclusion of this article validates the ongoing trends of global sustainable studies in nature-based solutions and social-ecological systems, highlighting the issue of environmental equity evaluation.